The Role of Source Credibility and Place Attachment in Enhancing Visitors' Satisfaction - Roostika, Ratna; Muafi, Muafi (SBM ITB, 2014)
Abstract. Tourism is one of the important tools for development. In order to survive, credible resources and place attachment are keys for today's competition in the tourism sector. The objective of this study is to assess the relationships among source credibility, place attachment, and visitors' satisfaction. The study surveyed visitors in the World Heritage Site (WHS) Borobudur. Borobudur as a premium destination in Indonesia should be well managed so that it will strongly create attachment among visitors. A valid 132 questionnaires were analyzed using Partial Least Squares – Structural Equation Modeling. All the proposed relationships were supported meaning that the important role of both credible resources and place attachments to visitors' satisfaction was confirmed. The findings offer important implications where Government and tourism agency should take priority on the importance of source credibility and engaging marketing approaches for building place attachment. For academic, this study enriches and provides empirical evidence on the relationships proposed to the tourism and marketing literature.Keywords: Source credibility, Place attachment, Satisfaction, WHS Borobudur.Abstrak. Pariwisata adalah salah satu senjata penting untuk pembangunan. Untuk bisa bertahan dalam persaingan pariwisata, kemampuan menawarkan sumber daya/informasi yang credible dan mendapatkan rasa keterikatan dari wisatawan sangat penting. Tujuan penelitian ini adalah menganalisis hubungan antara sumber daya yang kredible, rasa keterikatan terhadap tempat, dan kepuasan wisatawan. Responden adalah pengunjung di kompleks Candi Borobudur. Survey dalam studi ini mengolah 132 data yang valid. Metode Structural Equation Modeling dengan Partial Least Squares dipilih untuk menganalisis data kuantitatif dan membuktikan hipotesa yang dikembangkan. Hasil analisis menunjukkan keempat hipotesis dapat diterima. Hal ini membuktikan pentingnya peran sumber daya kredibel dan rasa keterikatan destinasi terhadap kepuasan wisatawan. Implikasi terhadap pengelola pariwisata Borobudur dan pemerintah adalah untuk menekankan pentingnya mendapatkan kepercayaan dan respon positif wisatawan lewat penawaran wisata dan informasi yang kredibel serta penggunaan pendekatan pemasaran yang efektif. Secara teori menyumbangkan kekayaan literature di bidang pariwisata dan pemasaran terkait peran kredibilitas informasi dan rasa keterikatan terhadap kepuasan wisatawan.Kata kunci: Borobudur, Rasa keterikatan tempat, Kredibilitas sumber daya, Kepuasan wisatawan.